DEGRADASI BUDAYA DALAM UPACARA PERKAWINAN MASYARAKAT NIAS DI DENPASAR - Gulo, Adil Niat (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies); Volume 01, Nomor 01, Desember 2012, 2013)
Every man in the world cannot be separated from culture. Human and culture are a partner that cannot be separated. There is no culture without man and and there is no man without a culture. So they also nias, the role of culture in a ceremony of marriage is very important. Prove to be in every the mating exercised refers it always to the rules that apply to public nias customary compliance with that which is inherited by their fathers. But in fact for people Nias who live in areas perantauan esp. living in a municipality Denpasar experienced degradation in the ceremony of marriage. Prove to be in every marriage performed only perform the ceremony of invocations in the church and reception in the building. On things for people Nias ritual of customary this is very important from the rites of the other. Society Nias who live in areas nias a ceremony that first one was done any there was a wedding is ritual of customary, will be followed with with a procession of invocations in the church. Of the above occurred, caused by the influence of globalization as the development of education, technology and media, the environment and the younger generation, the absence of knowledge about a ceremonial procession marriage.
Keywords: The degradation of culture, the ceremony of marriage, society Nias